Microscale thermophoresis provides insights into mechanism and thermodynamics of ribozyme catalysis - Gaffarogullari, Ece Cazibe; Krause, André; Balbo, Jessica; Herten, Dirk-Peter; Jäschke, Andres (RNA biology, 2013)
The analysis of binding interactions between small molecules and biopolymers is important for understanding biological processes. While fluorescence correlation spectroscopy (FCS) requires fluorescence labeling on the small molecule, which often interferes with binding, in microscale thermophoresis (MST) the label can be placed on the biopolymer. Ribozymes have not been analyzed by MST so far. The Diels-Alderase ribozyme (DAse) is a true catalyst, facilitating the Diels-Alder reaction between two free small substrates, anthracene dienes, and maleimide dienophiles. Despite high efforts, the determination of the dissociation constant (KD) of maleimide dienophiles to the DAse by FCS has been unsuccessful. Here, we determined the binding interactions of the DAse to its substrates and the Diels-Alder product using MST. The results supported a positive cooperativity for substrate binding to the DAse. By varying the temperature, we furthermore studied the thermodynamics of dienophile dissociation. The entropic contribution was found to be the energetic driving force for the binding of the dienophile to the DAse.
Gesehen am 04.03.2021